Thyrotoxicosis factitia: a rare cause of junctional rhythm and cardiac arrest - Sohaib Roomi; Waqas Ullah; Iqra Iqbal; Asrar Ahmad; Sameer Saleem; Zeeshan Sattar (Greater Baltimore Medical Center, 2019)
Thyrotoxicosis factitia is a hyperthyroid state due to the accidental or deliberate thyroxine ingestion. It can have many complications depending upon the organ involved. We present a case of a heavy built athlete presenting with cardiac arrest, who was found to be abused the thyroxine hormone for bodybuilding. Electrocardiogram (EKG) was significant for junctional arrhythmias along with interval supraventricular tachycardia (SVT) and bradycardia. The patient ultimately expired due to a failed resuscitation. To our knowledge, this is the first reported case of junctional arrhythmias caused by exogenous thyroxine.